IoT Based Early Forest Fire Detection and Monitoring System - Sobana, S.; Seerangurayar, T.; Bharathraj, M.; Bhanu Sagar, K. V.; Kumar, Suraj (Indian Forester, 2024)
Forest fires have become a serious concern throughout the world, causing damage to natural environment and forest ecosystems such as greenhouse effect and climatic changes. Therefore detection of forest fires at their initial stage becomes important. Satellite-based surveillance is used to detect a forest fire in a massive area. This method is slightly inefficient. The main objective of this Early Forest Fire Detection System is to develop a system that prevent from fire by alerting forest officials through SMS as soon as the fire is detected which in turn can be used to reduce the outspread of the forest fire. The location of the fire can be known through SMS using the GSM module and GPS. The outspread of the forest fire can also be reduced by a pump-based mechanism to split the water into the fired bushes and the plants. For this purpose, the system must be built with a water storage system to save rainwater to implement this method. During the forest fire, animals and birds in that forest can be warned by a high-pitched speaker to repel the animals and birds from that location. The system also contains a smoke sensor, temperature sensor, and flame sensor. The system is powered by solar and battery. By constantly monitoring the temperature we can stop the forest fire on an early basis.